Antioxidant capacity of foods for scavenging reactive oxidants and inhibition of plasma lipid oxidation induced by multiple oxidants. Issue 5 (19th April 2016) - Niki, Etsuo
Abstract : Antioxidant capacity is assessed by the rate and amount of scavenging oxidants and inhibition of lipid oxidation induced by multiple oxidants. Abstract : Unregulated oxidation of biological molecules induced by multiple oxidants has been implicated in the pathogenesis of various diseases. Consequently, the effects of antioxidants contained in foods, beverages and supplements on the maintenance of health and prevention of diseases have attracted much attention of the public as well as scientists. However, recent human studies have shown inconsistent results and failed to demonstrate the beneficial effects of antioxidants. The mechanisms and dynamics of antioxidant action and assessment of antioxidant capacity have been the subject of extensive studies and arguments. In the present article, the antioxidant capacity has been reviewed focusing on two main issues: the capacity of antioxidants to scavenge multiple reactive oxidants and to inhibit plasma lipid oxidation induced by different biological oxidants. It is emphasized that the capacity of antioxidants to scavenge reactive oxidants does not always correlate linearly with the capacity to inhibit lipid oxidation and that it is necessary to specify the oxidant to assess the efficacy of antioxidants, since multiple oxidants contribute to oxidative damage in vivo and the effects of antioxidants depend on the nature of oxidants. A convenient and rapid method using a microplate reader is discussed for assessing the antioxidant capacity against plasma lipid oxidation induced by multiple oxidants including peroxyl radicals, peroxynitrite, hypochlorite, 15-lipoxygenase, and singlet oxygen.